(untitled) (Research, Society and Development, 2022)
Suicide is characterized as a deliberate, conscious, and intentional act, in which the individual takes his or her own life due to the combination of several biological, social, and psychological factors, representing a major public health problem worldwide. Objective: To analyze the epidemiological profile of suicide cases in a municipality in the midwest of Santa Catarina State, registered in the TabNet database, in the period from 2017 to 2021. Methodology: Descriptive, exploratory, quantitative and retrospective character. It was carried out in Caçador - SC, having as sample the total number of deaths by suicide that occurred in the studied period, obtained through the SIM made available in the DATASUS databases. Results: It was possible to identify that 51 people took their own lives. The profile of individuals who have a greater tendency to commit suicide was: men, single, white, in the age group between 20 to 39 years and between 60 to 69 years, predominantly by hanging, followed by strangulation and suffocation, with education level between 8 to 11 years, without medical assistance and occurrence in their home. The highest incidence rate observed occurred in the year of 2018 (1.67 cases) and the prevalence rate in the study period was 6.37 cases per 10,000 inhabitants. Conclusion: The study had as limitations its descriptive nature, ignored data, and the underreporting of suicides. It is essential to encourage discussions on the subject and create effective public policies for health promotion and suicide prevention, as well as the development of intersectoral actions articulated in a network system.